Integration of BIM work culture for improving global project collaboration productivity - Abdul Ghafar, Maszura; Shari, Zalina; Ibrahim, Rahinah; Rahimian, Farzad Pour (IGI Publishing Hershey, 2018)
Building information modelling is further globalizing architecture, engineering, and construction (AEC) professional partnerships. However, little is known on the effect of cultural and human factors on BIM-enabled visualization applications. This desktop study examined the extant literature on factors relating to application of BIM-enabled visualization technologies as a process that can improve, leverage, and conduct visual communication for coordination during implementation of global projects. It identifies BIM-enabled visualization having the capability in facilitating knowledge flows in complex discontinuous working environment of a property development-s life cycle, and supports designers- understanding in its early working phases. This chapter presents the development of a theoretical proposition for embedding local work culture etiquette in BIM-enabled visualization application for augmenting dynamic knowledge transfer among discontinuous members in a building project. The result is expected to benefit rapidly developing countries (e.g., Malaysia) in enabling successful partnerships with counterparts from developed countries.